Aesthetics Contents of Data Visualization as an Input to its humanization (Al-Academy, 2023)
The aesthetic contents of data visualization is one of the contemporary areas through which data scientists and designers have been able to link data to humans, and even after reaching successful attempts to model data visualization, it wasn't clear how that reveals how it contributed to choosing the aesthetic content as an input to humanize these models, so the goal of the current research is to use The analytical descriptive approach aims to identify the aesthetic contents in data visualization, which the researchers interpreted through pragmatic philosophy and Kantian philosophy, and analyze a sample of data visualization models to reveal the aesthetic entrances in them to explain how to humanize them. The two researchers reached several results, namely the application of ornamentation and geometric abstraction through the entrance of mathematical abstraction based on individual perception in Kant's philosophy of sublimeness. Community icons and inherited traditions were also utilized through the entrance of life events based on collective experience in pragmatic philosophy. Both approaches lead to Aesthetic excitement and a sense of pleasure due to its access to human realities.